Hepatitis B virus DNA integration occurs early in the viral life cycle in an in vitro infection model via NTCP-dependent uptake of enveloped virus particles - Tu, Thomas; Budzinska, Magdalena A.; Vondran, Florian; Shackel, Nicholas A.; Urban, Stephan (Journal of virology, 2018)
Chronic infection by hepatitis B virus (HBV) is the major contributor to liver disease worldwide. Though HBV replicates via a nuclear episomal DNA (covalently closed circular DNA [cccDNA]), integration of HBV DNA into the host cell genome is regularly observed in the liver in infected patients. While reported as a prooncogenic alteration, the mechanism(s) and timing of HBV DNA integration are not well understood, chiefly due to the lack of in vitro infection models that have detectable integration events. In this study, we have established an in vitro system in which integration can be reliably detected following HBV infection. We measured HBV DNA integration using inverse nested PCR in primary human hepatocytes, HepaRG-NTCP, HepG2-NTCP, and Huh7-NTCP cells after HBV infection. Integration was detected in all cell types at a rate of >1 per 10,000 cells, with the most consistent detection in Huh7-NTCP cells. The integration rate remained stable between 3 and 9 days postinfection. HBV DNA integration was efficiently blocked by treatment with a 200 nM concentration of the HBV entry inhibitor Myrcludex B, but not with 10 μM tenofovir, 100 U of interferon alpha, or a 1 μM concentration of the capsid assembly inhibitor GLS4. This suggests that integration of HBV DNA occurs immediately after infection of hepatocytes and is likely independent of de novo HBV genome replication in this model. Site analysis revealed that HBV DNA integrations were distributed over the entire human genome. Further, integrated HBV DNA sequences were consistent with double-stranded linear HBV DNA being the major precursor. Thus, we have established an in vitro system to interrogate the mechanisms of HBV DNA integration., IMPORTANCE Hepatitis B virus (HBV) is a common blood-borne pathogen and, following a chronic infection, can cause liver cancer and liver cirrhosis. Integration of HBV DNA into the host genome occurs in all known members of the Hepadnaviridae family, despite this form not being necessary for viral replication. HBV DNA integration has been reported to drive liver cancer formation and persistence of virus infection. However, when and the mechanism(s) by which HBV DNA integration occurs are not clear. In this study, we have developed and characterized an in vitro system to reliably detect HBV DNA integrations that result from a true HBV infection event and that closely resemble those found in patient tissues. Using this model, we showed that integration occurs when the infection is first established. Importantly, we provide here a system to analyze molecular factors involved in HBV integration, which can be used to develop strategies to halt its formation.
Gesehen am 28.04.2022